Evaluation of hypercholesterolemia management in at-risk patients by cardiologists in France: a case vignette-based study - Jean Ferrieres; Eric Bruckert; Michel Farnier; Michel Krempf; Jean-Jacques Mourad; Baptiste Roux; Francois Schiele (Becaris Publishing Limited, 2023)
Aim: This online interactive survey investigated lipid-lowering approaches of French cardiologists in highand very high-cardiovascular risk patients with hypercholesterolemia. Materials & methods: Physicians assessed three hypothetical patients at three clinic visits, and selected the patients' cardiovascular risk category, target low-density lipoprotein cholesterol (LDL-C) and treatment. Results: A total of 162 physicians completed 480 risk assessments; 58% of assessments correctly categorized the hypothetical patients. Most physicians chose the correct LDL-C target for one of the very high-risk patients, but higherthan- recommended targets were selected for the other very high-risk patient and the high-risk patient. Statins were the most commonly chosen treatment. Conclusion: French cardiologists often underestimate cardiovascular risk in patients with hypercholesterolemia, select a higher-than-recommended LDL-C target and prescribe less intensive treatment than that recommended by guidelines.